Wacana Debat Inklusif: Menyoal Jadal Sebagai Perdebatan Dalam Al-Qur’an - Kamarusdiana Kamarusdiana; Amiruddin Nahrawi (Al Ashriyyah, 2020)
Debate cannot be avoided and denied in the reality of the reality of today's social life. Because basically human conditions and situations are in an inequality or different sociologically and psychologically. Included in the Koran also illustrates the dialogue process and debate that is quite serious about the truth. The position of debate in the Qur'an is called Jadal. Jadal was born from the interaction and historical dynamics in the process of the decline of the Qur'anic teachings. On the other hand, debate is not and can be carried out without a method. If that happens, the hope of the debate process will not be reached. The forerunner to success in the debate is due to the implementation of the right method. However, the debate should be built on the basis of togetherness in order to create an inclusive debate. It has become an ideal in the Qur'an about the process of debate and an inclusive diaologist.